KESIAPAN PENERAPAN KURIKULUM MERDEKA DI MI KHADIJAH BANJARMASIN - Nur Fajariah (Titik Fokus Karya, 2023)
There are efforts to renew and improve the quality of government education to ensure that it implements a new curriculum, namely the independent curriculum as a complement to the previous curriculum. Decree (SK) of the Directorate General of Islamic Education Number 3811 of 2022 concerning Madrasas Implementing an Independent Curriculum for the 2022/2023 Academic Year outlines the requirements for madrasas that use an independent curriculum. Some madrasas have registered their madrasas as schools for implementing the independent curriculum, but there are still many madrasas that have not registered their madrasas as implementing madrasas for the independent curriculum. This study aims to discuss the readiness of Madrasah Ibtidaiyah Khadijah Banjarmasin in implementing the Independent Curriculum. This research is a qualitative descriptive study. The subjects of this study were the teacher council, the head of the madrasah, and the deputy head of the madrasah curriculum division at MI Khadijah Banjarmasin. Data collection techniques used are through observation, interviews, and documentation. The results showed that graduate competency standards, content standards, process standards, educational assessment standards, educational staff standards, facilities and infrastructure standards, management standards, and financing standards at MI Khadijah Banjarmasin were not ready for the implementation of the independent curriculum.